Effect of thermo-mechanical conditions during constrained friction processing on the particle refinement of AM50 Mg-alloy phases - Camila Caroline de Castro; André Martins Neves; Benjamin Klusemann (Journal of Magnesium and Alloys, 2024)
Constrained Friction Processing (CFP) is a novel solid-state processing technique suitable for lightweight materials, such Mg- and Al-alloys. The technique enables grain size refinement to fine or even ultrafine scale. In this study, the effect of CFP on the microstructural refinement of AM50 rods is investigated in terms of particle size and morphology of the eutectic and secondary phases originally present in the base material, in particular the eutectic β-Mg17Al12 and Al-Mn phases. For that purpose, as-cast and solution heat-treated base material and processed samples were analyzed. The Al8Mn5 intermetallic phase was identified as the main secondary phase present in all samples before and after the processing. A notorious refinement of these particles was observed, starting from particles with an average equivalent length of a few micrometers to around 560 nm after the processing. The refinement of the secondary phase refinement is attributed to a mechanism analogous to the attrition comminution, where the combination of temperature increase and shearing of the material enables the continuous breaking of the brittle intermetallic particles into smaller pieces. As for the eutectic phase, the results indicate the presence of the partially divorced β-Mg17Al12 particles exclusively in the as-cast base material, indicating that no further phase transformations regarding the eutectic phase, such as dynamic precipitation, occurred after the CFP. In the case of the processed as-cast material analyzed after the CFP, the thermal energy generated during the processing led to temperature values above the solvus limit of the eutectic phase, which associated with the mechanical breakage of the particles, enabled the complete dissolution of this phase. Therefore, CFP was successfully demonstrated to promote an extensive microstructure refinement in multiple aspects, in terms of grain sizes of the α-Mg phase and presence and morphology of the Al-Mn and eutectic β-Mg17Al12.